2011
DOI: 10.1128/jb.01312-10
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis Can Utilize Heme as an Iron Source

Abstract: Most iron in mammals is found within the heme prosthetic group. Consequently, many bacterial pathogens possess heme acquisition systems to utilize iron from the host. Here, we demonstrate that Mycobacterium tuberculosis can utilize heme as an iron source, suggesting that M. tuberculosis possesses a yet-unknown heme acquisition system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
102
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(110 citation statements)
references
References 31 publications
8
102
0
Order By: Relevance
“…S2 B and C). These results ruled out the possibility that the previously observed lack of growth of Mtb siderophore mutants (15,19) was a result of insufficient amounts of soluble iron and demonstrated that low-affinity iron uptake is not capable of promoting the growth of Mtb in the absence of siderophores. This is consistent with the absence in Mtb of all known components of iron ion uptake systems of M. smegmatis, such as the putative ferric and ferrous inner membrane transporters and the Mycobacterium smegmatis porin A (MspA)-like porins in the outer membrane (20).…”
Section: Resultsmentioning
confidence: 43%
See 1 more Smart Citation
“…S2 B and C). These results ruled out the possibility that the previously observed lack of growth of Mtb siderophore mutants (15,19) was a result of insufficient amounts of soluble iron and demonstrated that low-affinity iron uptake is not capable of promoting the growth of Mtb in the absence of siderophores. This is consistent with the absence in Mtb of all known components of iron ion uptake systems of M. smegmatis, such as the putative ferric and ferrous inner membrane transporters and the Mycobacterium smegmatis porin A (MspA)-like porins in the outer membrane (20).…”
Section: Resultsmentioning
confidence: 43%
“…S1]. One possible explanation is that Mtb cannot use iron salts without siderophores, as observed previously with some siderophore biosynthesis mutants (15,16) but not with others (17). Even 100 mM ferric citrate failed to stimulate the growth of Mtb siderophore biosynthesis mutant ΔmbtD::hyg, whereas the Mycobacterium smegmatis siderophore biosynthesis mutant ΔfxbA::hygΔmbtD::kan (18) was rescued by 50 μM ferric citrate (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 85%
“…To obtain iron, M. tuberculosis synthesizes and secretes high-affinity ferric iron chelators (mycobactins) (33), and in vitro, it also utilizes heme as an iron source (18,34). Although essential, iron can also be toxic, due to the ability of Fe 2ϩ to catalyze the generation of deleterious oxygen radicals from normal products of aerobic metabolism thorough the Fenton reaction (12,17).…”
mentioning
confidence: 99%
“…To test for Mt-DyP deferrochelatase activity, we utilized a mycobactindeficient M. tuberculosis strain, Mtb⌬mbtB, which has an interrupted mycobactin biosynthetic pathway to prevent siderophore-mediated iron acquisition (20,41) and cannot utilize Fe(III) in the absence of exogenous siderophore (mycobactin). Thus, Mtb⌬mbtB may only sequester iron via the heme uptake pathway.…”
mentioning
confidence: 99%